China’s Evolving New Third World Strategy in the Twenty-First Century - Bagale, Sharmila (Myagdi Guru, 2024)
This article seeks to examine China’s Third World Strategy from Mao-Deng-Xi’s political eras. The societal tensions emerged in China after 1949, which have arisen as a consequence of its rapid economic expansion in the twenty first century. While China continues to ascend and demonstrate a high potential for further progress, signs of a slowdown in its once-robust economic growth raise concerns about potential implications for social stability in specific regions. China's unparalleled economic presence and influence have been evident in its engagements across Africa, Asia, South Asia, and Latin America. This expansive involvement in the developing world has been a consistent component of Beijing’s foreign policy since the establishment of the People’s Republic of China in 1949. Notably, China’s foreign policy, particularly post- 1990, has remained actively engaged in South Asian regions, shaping a new reality with profound geopolitical implications. For this, it uses qualitative research method to inspect into the political and strategic transformations in regional governance triggered by the resurgence of the third world in Chinese foreign policy. The full extent of the impact of these developments on the world’s geopolitical landscape remains uncertain, making it a compelling area of exploration. The Belt and Road Initiative (BRI) is China’s new strategy for new third world strategy emerged to support the third world countries, and it is an aspiration to be a global power.